PERILAKU KOMUNIKASI NARAPIDANA WANITA BERSTATUS IBU RUMAH TANGGA DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II PEKANBARU - Habsari, Yashinta Wulan; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The high crime rate in the city of Pekanbaru is increasingly rising, one of which is shown by the increasing number of women prisoners in the Child Special Training Institutions Class II of Pekanbaru. Woman prisoners are dominated by women prisoners housewives. In interacting with fellow prisoners other women, there is a language and certain symbols that have been agreed. The purpose of this research is to determine the communication behavior of women prisoners housewives in Child Special Training Institutions Class II of Pekanbaru, as seen from the verbal and non verbal communication.This research used qualitative research method with descriptive analysis. The subject of research is consist of five women prisoners housewives, who has been choosen using by the purposive sampling technique. The data collection technique is done by in-depth interview, non participant observation, and documentation. The analysis data technique used interactive mode Huberman and Miles. Validity of the data used triangulation and perseverance observation.The results of this research are showed that the communication behavior of women prisoners housewives in Child Special Training Institutions Class II of Pekanbaru seen from verbal communication used Indonesian, Malay, Javanese and Betawi. And there is a nickname or a term such as